2021
DOI: 10.1002/jemt.23728
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Eurasian moorhen spleen: A comprehensive study using gross anatomy, light, and transmission electron microscopy

Abstract: The spleen is the largest secondary lymphoid organ with major roles in the removal of blood-borne antigens. The Eurasian moorhen is a wild aquatic bird that revealed the adaptation to harsh environmental conditions. Information regarding the structural features of moorhen's spleen is lacking. The present study aimed to describe the composition of moorhen's spleen using anatomical dissection, histology, histochemistry, immunohistochemistry, and transmission electron microscopy. The spleen appeared as a brownish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Zhang et al 5 reported a similar architecture of the spleen in adult broiler chickens in general. The trabeculae were poorly developed in other avian species like in ostrich, a non-flying bird (Struthio camelus) spleen 22 , Japanese quail (Coturnix coturnix Japonica) spleen 23 Eurasian moorhen (Gallinula chloropus, also known as the "swamp chicken") spleen 24 and Red-Legged Partridge (Alectoris chukar) spleen 25 . A significantly increasing trend in histomorphometrical parameters of capsule, white pulp and lymphatic nodules was observed in broiler chicken until post-hatch day 35.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 5 reported a similar architecture of the spleen in adult broiler chickens in general. The trabeculae were poorly developed in other avian species like in ostrich, a non-flying bird (Struthio camelus) spleen 22 , Japanese quail (Coturnix coturnix Japonica) spleen 23 Eurasian moorhen (Gallinula chloropus, also known as the "swamp chicken") spleen 24 and Red-Legged Partridge (Alectoris chukar) spleen 25 . A significantly increasing trend in histomorphometrical parameters of capsule, white pulp and lymphatic nodules was observed in broiler chicken until post-hatch day 35.…”
Section: Discussionmentioning
confidence: 99%
“…The wall thickness of different segments of the moorhen digestive tract was determined in microscopic images taken using the × 4 objective lens. The average number of glucagon, somatostatin, PHH3, and C.CASP3 IR cells per the area of 1 mm 2 of the mucosa of the esophagus, proventriculus, isthmus, ventriculus, duodenum, jejunum, ileum, ceca, and rectum were analyzed in microscopic images taken using the × 10 objective lens with the help of the area measurement and particle counting sections of the ImageJ software (National Institutes of Health, Bethesda, MD, USA) as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 34 ] The trabeculae, a branching network inside of spleen, emerge from all directions to support the arteries, veins, and splenic pulps. [ 35 ] Anatomically, the splenic pulps are constituted by three sub‐regions ( Figure ): red pulp (RP), white pulp (WP), and marginal zone (MZ). [ 36 ] (i) The RP mainly contributes to the capture of pathogens in the blood by various leukocytes such as DCs, MΦs, neutrophils, and NK cells.…”
Section: Significance Of Spleen‐targeting Vaccinationmentioning
confidence: 99%